When Satisfaction Is Not Enough to Build a Word of Mouth and Repurchase Intention - Kusuma, I Gusti Agung Eka Teja; Yasmari, Ni Nengah Wida; Agung, Anak Agung Putu; Landra, Nengah (APMBA (Asia Pacific Management and Business Application), 2021)
This study aims to measure the impact of service quality on word of mouth (WOM) and repurchase intention mediated by customer satisfaction. Design/methodology/approach: This cross-sectional study was conducted in all branches of Bank BPD Bali in Bali involving 91 Western Union customers at Bank BPD Bali as respondents. The research hypothesis was tested using a second order model processed by Structural Equation Modeling (SEM) analysis techniques with PLS software. Findings: Satisfaction has "tired" itself as a mediating buffer of quality of service to build loyalty or intention to buy back and word of mouth positive. The evidence shows, service quality has a positive and significant effect on word of mouth and repurchase intention, but satisfaction fails to mediate the effect of service quality on word of mouth and repurchase intention. Customer satisfaction does not affect word of mouth and repurchase intention Practical/implications: Service quality programs must be able to consider other effects besides satisfaction to build word of mouth and repurchase intention. Satisfaction is dynamic and difficult to maintain when competition is getting tougher.